The Penal Code And Criminal Procedure Code (Amendment) Act 1983 - Koh, Philip (Journal of Malaysian and Comparative Law, 2019)
The Penal Code And Criminal Procedure Code (Amendment) Act 1983 thereinafter "the Amendment Act" received Royal Assent on 18th February 1983 and became law upon being gazetted on 19th February 1983.